Evidence-based health care in Nepal: The importance of systematic reviews - van Teijlingen, Edwin Roland; Simkhada, Bibha; Ireland, Jillian C.M.; Simkhada, Padam P.; Bruce, Julie (Nepal Journal of Epidemiology, 2012)
Systematic reviewing involves a structured, rigorous, and objective approach to provide a critical synthesis of the available evidence in a particular field. This paper provides a guide to the key steps to undertake a systematic review. It describes the steps to search for relevant literature, provides advice on how to extract data, synthesize and then interpret data during the review process. It also provides the key references and guidelines which are commonly used for systematic review. It is important that researchers conduct and publish systematic reviews to help generate appropriate evidence to interventions and identify gaps in ‘local’ research. The authors argue that there is a place for systematic reviews in health services research in Nepal. Finally, this paper acknowledges that evidence should be considered within the local health situation and context. http://dx.doi.org/10.3126/nje.v1i4.5498 Nepal Journal of Epidemiology 2011;1(4):114-118